259. A Prospective, Stewardship-Driven IV to PO Conversion in Uncomplicated Bacteremia. (31st December 2020) - Quan, Asia; Marks, Gregory; Tran, Hai P; Shane, Rita; Ben-Aderet, Michael; Sutterwala, Fayyaz S; Grein, Jonathan; Smith, Ethan; Rapp, Jeffrey
Abstract: Background: Recent data has shown a transition to oral (PO) antibiotics (ABX) for definitive treatment of uncomplicated bacteremia has similar efficacy compared to continuation of intravenous (IV) ABX, and reduces hospital length of stay (LOS). The purpose of this study was to evaluate the safety and efficacy of an antimicrobial stewardship pharmacist-driven, IV to PO ABX transition in clinically stable patients with uncomplicated bacteremia, and to determine the impact on hospital LOS. Methods: This was a prospective, interventional study with concurrent controls, conducted at Cedars-Sinai Medical Center between November 2019 and April 2020. For patient recruitment, a report of all positive inpatient blood cultures was reviewed daily. For patients meeting study criteria, the treating provider was contacted to recommend an IV to PO ABX transition. The treating provider was responsible for making the final determination on ABX therapy. Patients continuing IV ABX served as the comparator group to those transitioning to PO. The primary outcome of interest was a composite of: 30-day, all-cause mortality, 30-day readmission due to infectious- or ABX-related complications, or 30-day recurrent infection with the same organism recovered. The second outcome of interest was overall hospital LOS and hospital LOS after the definitive ABX regimen was established. Results: A total of 117 patients were evaluated; 69 patients met criteria for inclusion in the study (46 PO ABX / 23 IV ABX). Overall, baseline characteristics were similar between the groups. No difference was observed in the 30-day composite outcome (1 in each group), but the median, overall hospital LOS was three days shorter in the PO group. Furthermore, hospital LOS after the definitive ABX regimen was established was four days shorter in the PO group. Based on the differences in hospital LOS observed, the intervention was estimated to have resulted in approximately $819, 200 cost-avoidance during the study period. Conclusion: Similar to prior studies, our findings support the safety and effectiveness of an IV to PO ABX transition in clinically stable patients with uncomplicated bacteremia. Antimicrobial stewardship pharmacists can be leveraged to facilitate such a transition. Disclosures: All Authors : No reported disclosures